Perencanaan Arsitektur Sistem Informasi SMP BIBS Menggunakan Enterprise Architecture Planning - Muhamad Wirapermana; Topan Setiawan (Ma'soem University, 2023)
The information system currently used at SMP Binar Ilmu Boarding School (BIBS) is only local. The applications used are still not integrated, and have different platforms and database types. This will greatly affect the speed and reliability in carrying out the process of collecting, storing, searching and processing data and also distributing information to school management.The purpose and objective of this research is to analyze the business needs of BIBS as a whole and align it with the school's strategy in order to create an integrated information system with the EAP method so as to produce a clear blueprint to support school governance in the use of information. Enterprise architecture planning is carried out by analyzing business processes at BIBS which include 3 main business processes, namely: New Student Admission, Teaching and Learning Process, and Student Graduation. As well as 3 supporting business processes, namely: Islamic Boarding School Management, ICT Management, and Counseling and Women's Talent Interest Development Management. The results of the research carried out are planning for school information system architecture at BIBS, in the form of recommendations for information system architecture development.